Complete mitochondrial genome and the phylogenetic position of the Caroun croaker Johnius carouna (perciformes: Sciaenidae) - Wei-Di Yang; Chang-Chang Guo; Min Liu; Baian Lin (Mitochondrial DNA. Part B. Resources, 2018)
In this study, the complete mitogenome of the Caroun croaker Johnius carouna was obtained. Its mitogenome is 18,752 bp in length, consisting of 37 genes with the typical gene order and direction of transcription in vertebrates. Gene rearrangement was found in J. carouna, same as another two Johnius species available in GenBank, J. distinctus (MF083699) and J. grypotus (KC491206). The overall nucleotide composition is: 24.2% A; 18.0% C; 21.4% G, and 36.4% T. Sizes of the 23 tRNA genes range from 67 to 75 bp. One start codons (ATG) and three stop codons (TAG, AGG, and TAA/TA/T) were detected in 13 protein-coding genes. In the Bayesian tree based on the complete mitogenomes of 21 species (including J. carouna) from the family Sciaenidae, all nodes were strongly supported. The result shows that J. carouna was placed as sister to the silver croaker J. grypotus of the same genus. The mechanism of gene rearrangement in the genus Johnius merits further investigation.